Incompatible magnetic and dielectric properties of BiCu3-xMnxTi4-yMyO12 (x = 0 & 0.5; y = 1 & 1.5 and M = Fe & Mn). Issue 5 (1st April 2020) - Haque, Ariful; Shukla, Ashish; Dutta, Uma; Ghosh, Debamalya; Gayen, Arup; Mahata, Partha; Vasundhara, M.; Kundu, Asish K.; Seikh, Md Motin
Abstract: Here we report ambient pressure synthesis, magnetic and dielectric properties of BiCu3 Ti3 (Fe/Mn)O12 and BiCu2.5 Mn0.5 Ti2.5 Fe1.5 O12 . Both the samples are crystallized in a cubic I m-3 space group. The antiferromagnetic ground state of A-site copper in Bi2/3 Cu3 Ti4 O12 is differently affected by substitution of nonmagnetic Ti 4+ by magnetic Fe and Mn ions in B-site. In contrast to the Mn substitution, the antiferromagnetic ordering of A-site Cu is robust towards Fe substitution. The substitution of iron for Ti 4+ initially weakens the antiferromagnetic structure of A-site Cu and eventually it results in the crossover from antiferromagnetic to ferrimagnetic state, whereas the Mn substitution quickly turns antiferromagnetic to ferrimagnetic state. For x > 1.0 Fe-doped sample and low Mn-doped samples exhibit phase separation where the ferromagnetic like phase coexists with antiferromagnetic phase. The glassy magnetic state is realized for x = 1.0 Fe doped sample. The magnetic ground state strongly influences the dielectric behavior of the samples. Near room temperature the dielectric constant value is 2000 for BiCu3 Ti3 FeO12, whereas for BiCu2.5 Mn0.5 Ti2.5 Fe1.5 O12 the value is much lower (<600) with higher dielectric loss. The leaky nature in magnetically phase separated BiCu2.5 Mn0.5 Ti2.5 Fe1.5 O12 can be ascribed to the opening of conducting ferrimagnetic channels. The present investigation revealed that in quadruple perovskite the magnetic and dielectric properties are incompatible where improvement of magnetic response eventually suppresses the dielectric behavior.